PENINGKATAN KEMAMPUAN BERFIKIR KRITIS SISWA MELALUI METODE SQ3R PADA SISWA KELAS 4C NAHDLOTUL ULAMA - aministia, nur aemi; amalia, Nur fitri (Universitas Islam Zainul Hasan Genggong, 2023)
Grade IV students at MI Nahdlotul Ulama have difficulties in summarizing narrative texts in Indonesian. Of the 29 students there were 9 students or 29 percent who achieved a completeness score of 75. This shows that as many as 21 students or 71 percent of students were still not finished. One alternative problem solving that can be done by the teacher is to apply the SQ3R strategy. This research was carried out using a qualitative approach with the type of Classroom Action Research (CAR). This research was conducted in 2 cycles. Each cycle consists of several stages, namely: planning, implementing, observing, and reflecting. Data collection techniques include interviews, observations, tests, and documentation. The steps of data analysis, namely: data collection, data reduction, and drawing conclusions. The results of the research showed that the average percentage of students' activity during the reading process of SQ3R cycle I was 78 percent and cycle II was 89 percent. While the average value of the completeness of the reading process in the first cycle is 57 percent and 90 percent in the second cycle. Based on these results it can be concluded that the implementation of the SQ3R strategy in learning Indonesian has been carried out properly.